Identificação do ambiente inovador em empresas que adotam um modelo de gestão da inovação padronizado: um estudo em pequenas e média empresas cearenses - Pompeu Filho, Persival Lopes (2014)
This research aims to identify how a model of innovation management enables the development of an innovative environment within companies who apply. Aiming to evaluate the contributions of a standardized management model innovation for the development of an innovative environment. His theoretical framework of basic concepts of innovation, innovation management, viewing models of innovation management and characterization of a specific management model applied in Ceará companies. Finally it discusses the innovative environment and its characteristics in five separate constructs: vision and leadership for innovation, organizational structure for innovation, management of resources for innovation, process management, transactions and ideas for innovation for innovation and results. For the research, a qualitative approach, the strategy of multiple case studies was used, from semistructured interviews (with a structured questionnaire derived model of MIS ), triangulated with document analysis and direct and participant observation, based on theoretical framework obtained in theoretical reasoning. As a research subject had were three small and medium businesses that adopt the standard model "GESTINNO ". The results showed that although the management model that adopt significantly contribute to the growth and thinking towards innovation, companies surveyed still have much to improve regarding the development of an innovative environment, characterized that the standard model "forgets " this question, focusing on formal management processes.